Multiple improvement in piezoelectricity, ferroelectricity, and fluorescence of 0.94(Bi0.984Er0.016Na)0.5TiO3–0.06BaTiO3 by optimizing sintering temperature/dwell time. Issue 1 (29th September 2015) - Lei, Fengying; Zou, Xiao; Wen, Rui; Liu, Mengli; Zheng, Qiaoji; Jiang, Na; Luo, Lingling; Lin, Dunmin
Abstract : Multifunctional ceramics of 0.94(Bi0.984 Er0.016 Na)0.5 TiO3 –0.06BaTiO3 were prepared by a conventional ceramic technique. The effects of sintering temperature ( T s ) and dwell time ( t s ) on the ferroelectricity, piezoelectricity, and fluorescence of the ceramics were studied. Furthermore, the influence of poling electrical field on the up‐conversion emission intensities was also discussed. As T s and t s increase, the grains grow larger gradually and evolve from spheroid to rectangular shape. By increasing T s and t s, the ferroelectricity of the ceramics is improved and the remnant polarization P r increases. The optimum sintering temperature and dwell time for the piezoelectricity of ceramics are 1200 °C and 2 h, respectively. Also, both of the sintering temperature and dwell time make an important influence on the fluorescence of the ceramics. The ceramics sintered at 1140–1160 °C for 2 h possess excellent up/down‐conversion fluorescence. The up‐conversion emission intensity of the ceramics is further enhanced by optimizing poling electric field. This work develops a kind of multifunctional material that simultaneously possesses good ferroelectricity/piezoelectricity and excellent up/down‐conversion fluorescence by optimizing sintering temperature and dwell time.